Morphology and molecular phylogeny of Bindiferia gen. nov. (Dinophyceae), a new marine, sand-dwelling dinoflagellate genus formerly classified within Amphidinium. Issue 6 (2nd November 2021) - Borchhardt, Nadine; Chomérat, Nicolas; Bilien, Gwenael; Zentz, Frédéric; Rhodes, Lesley; Murray, Shauna A.; Hoppenrath, Mona
ABSTRACT: As historically described, the genus Amphidinum has long been recognized to be polyphyletic. Amphidinium sensu lato is the most diverse of all marine benthic dinoflagellate genera and after the redefinition of the sensu stricto genus about 100 species remained of unknown generic affiliation. A species similar to the Australian sensu lato species Amphidinium boggayum was discovered in France. Morphological and molecular phylogenetic data supported the description of a new species and the classification of the two closely related species within a new athecate, photosynthetic, benthic genus, named Bindiferia . Cells were dorsoventrally flattened with smaller asymmetric epicone. The cingulum was descending. The sulcus reached the antapex and had an extension onto the epicone. The apical structure complex formed an anticlockwise loop around the apex. A red stigma was located in the anterior part of the epicone, near the apex. Vegetative division occurred in a non-motile stage within a hyaline sheath. Non-motile cells had dorsal hypocone grooves. The two species differed from each other in epicone size, cingulum displacement, nucleus location and surface groove occurrence. The molecular phylogenetic results showed that Bindiferia is a distinct taxon that is only distantly related to Amphidinium sensu stricto . The nearest sister group to Bindiferia could not be reliably determined, but the apical structure complex suggested a close relationship to the genera of the Gymnodinium sensu stricto clade.